Shape of the nappe during free overfall from a rectangular channel with zero bed slope - Zachoval, Zbyněk; Böhm, Petr; Pařílková, Jana; Šafář, Robert; Šulc, Jan (Institute of Hydrology of the Slovak Academy of Sciences, Institute of Hydrodynamics of the Academy of Sciences of the Czech Republic, 2013)
The paper deals with selected procedures used to calculate the shape of compact nappe during free overfall from a smooth horizontal channel with rectangular cross section. Calculated and measured water surface and velocity conditions in the end section, the level of water surface upstream in front of the end section and the shape of the compact part of an overfall nappe are described for a particular compared case.

The paper deals with selected procedures used to calculate the shape of compact nappe during free overfall from a smooth horizontal channel with rectangular cross section. Calculated and measured water surface and velocity conditions in the end section, the level of water surface upstream in front of the end section and the shape of the compact part of an overfall nappe are described for a particular compared case.
Shape of the nappe during free overfall from a rectangular channel with zero bed slope
Keywords: Nappe shape; end depth; free overfall; confined nappe; unconfined nappe; numerical modelling; experimental measurement; Nappe shape; end depth; free overfall; confined nappe; unconfined nappe; numerical modelling; experimental measurement